2004
DOI: 10.1523/jneurosci.4710-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Molecular Atlas of the Hippocampus Using DNA Microarrays and High-ThroughputIn SituHybridization

Abstract: The hippocampus consists of a series of cytoarchitecturally discrete subregions that can be distinguished from one another on the basis of morphology, connectivity, and electrophysiological properties. To understand the molecular underpinnings for these differences, DNA microarrays were used to find genes predicted to be enriched in subregions CA1, CA3, and the dentate gyrus, and Ͼ100 of these genes were subsequently analyzed using in situ hybridization to obtain cellular-level localization of their transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
260
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(280 citation statements)
references
References 40 publications
17
260
1
2
Order By: Relevance
“…Specifically, the technique of high-throughput in situ hybridization has made it possible to compare the expression patterns of hundreds to thousands of genes across the subfields of the structure. These studies have shown that the pyramidal cells in CA3, CA2, and CA1 have distinct molecular identities, and while it remains difficult to make the leap from protein to computation, the data largely agrees with Cajal's original boundaries of the CA fields [48,103] (Figure I).…”
Section: Box 2: Genes In Circuitssupporting
confidence: 57%
“…Specifically, the technique of high-throughput in situ hybridization has made it possible to compare the expression patterns of hundreds to thousands of genes across the subfields of the structure. These studies have shown that the pyramidal cells in CA3, CA2, and CA1 have distinct molecular identities, and while it remains difficult to make the leap from protein to computation, the data largely agrees with Cajal's original boundaries of the CA fields [48,103] (Figure I).…”
Section: Box 2: Genes In Circuitssupporting
confidence: 57%
“…For example, in the hippocampus it is expressed largely in the CA1 stratum pyramidale (Fig. 2C, Inset), a region containing excitatory pyramidal neurons of different physiological and molecular identities (29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%
“…Along these lines, area CA2 expresses high levels of STEP (Boulanger et al, 1995); yet, unlike the hilus, it is relatively resistant to excitotoxic cell death (Zhang et al, 1997;El Bahh et al, 1999). Mechanistically, it is not known why CA2 neurons are resistant, although numerous studies have shown that CA2 pyramidal neurons are enriched in an array of receptors and trophic factors (Tucker et al, 1993;Ochiishi et al, 1999;Lein et al, 2005) that may affect excitability and/or provide trophic support and thus decrease susceptibility to excitotoxic stimuli. Likewise, divergence also holds at the level of synaptic afferents (Haglund et al, 1984;Köhler et al, 1985).…”
Section: Discussionmentioning
confidence: 99%